An Introduction to Phytoplanktons: Diversity and Ecology - Pal, Ruma; Choudhury, Avik Kumar (2014)
The book , 'An Introduction to Phytoplanktons - Diversity and Ecology' is very useful as it covers wide aspects of phytoplankton study including the general idea about cyanobacteria and algal kingdom. It contains different topics related to very basic idea of phytoplanktons such as, types ,taxonomic description and the key for identification et cetera Together with it, very modern aspects of phytoplankton study including different methodologies needed for research students of botany, ecology, limnology and environmental biology are also included. The first chapter is very basic and informative and describes algal and phytoplankton classification, algal pigments, algal bloom and their control, algal toxins, wetlands algae, ecological significance of phytoplanktons etc. A general key for identification of common phytoplankton genera is also included for students who will be able to identify these genera based on the light microscopic characters. In Chapters 2-4, different aspects of phytoplankton research like primary productivity, community pattern analysis and their ecological parameter analysis have been discussed with detailed procedures. Statistical analysis is also discussed in detail. Chapter 5 includes case studies related to review, phytoplankton diversity and dynamics.
1. A Brief Introduction to Phytoplanktons -- 2. Physico- Chemical Environment of Aquatic Ecosystem -- 3. Phytoplanktons and Primary Productivity -- 4. Community Pattern Analysis -- 5. Case Study -- 6. Glossary -- 7. Bibliography.
Keywords: Aquatic ecology; Biodiversity; Botany; Ecology; Freshwater; Marine sciences; Plant science; Plant systematics; Plant taxonomy; Plant Sciences; Biodiversity; Ecology; Freshwater & Marine Ecology; Marine & Freshwater Sciences; Plant Systematics/Taxonomy/Biogeography.